An experimental and simulation investigation into the energy balance and material balance characteristics in a fluidized bed heat exchanger. (September 2020) - Ji, Xuanyu; Lin, Weijian; Yan, Hui; Lin, Shunhong; Yang, Yu; Tian, Ye; Xu, Ming; Kang, Yinhu; Li, Jianbo
Graphical abstract: Flowchart for the solving procedure of cell model. Highlights: A cell model along the solids horizontal movement direction was established in the FBHE. The energy balance and material balance of the FBHE was investigated. The cell model was verified experimentally to be accurate under test conditions. Impacts of key structural and operational parameters were studied and discussed. Abstract: In the small-scale industrial CFB(SICFB) boiler, the furnace height is limited, the fuel particles can't be burned out in the furnace completely. So the circulating solid particles would combust in the external loop including the cyclone and the external fluidized bed heat exchanger(FBHE). Moreover, there's a macroscopic horizontal movement of circulating solid particles exists in the FBHE from its inlet to outlet. Under the impacts of combustion, heat transfer and particles attrition, parameters such as the bed temperature, combustion products concentrations, solids physical properties and heat transfer coefficient are changed along the solids movement direction. In this research, a one-dimensional cell model along the solids horizontal movement direction was established in the FBHE of a industrial CFB test-rig. The distributions, as well as the variations of the above parameters were calculated and analyzed based on the energy balance and material balance in each cell. The calculation results were compared with the experimental results to be validated. The energy balance and material balance characteristics of the FBHE were obtained accordingly. These results can provide referential materials for design and operation of the FBHE in small-scale industrial CFB system.